Phylum Xenacoelomorpha Philippe, et al., 2011. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Tyler, Seth; Schilling, Stephen (Zootaxa, 2011)
-